Методика оценивания в компьютерной системе тестирования знаний - Шкиль, A. C.; Напрасник, С. В.; Чумаченко, С. В. (УАДО, 2002)
The issues of knowledge evaluation in a learning testing system are considered. The developed system uses questions with several numbers of alternate answers in one seance. The formula of range limits calculation of rating scale is offered. It depends on a number of questions in a testing seance, a number of alternatives in each question and a number of marks in a rating scale. The factor of random selection of answers is taken into account in the proposed formula
Keywords: тестирование знаний; образование